A new way of assessing arm function in activity using kinematic Exposure Variation Analysis and portable inertial sensors – A validity study. (February 2016) - Ertzgaard, Per; Öhberg, Fredrik; Gerdle, Björn; Grip, Helena
Abstract: Portable motion systems based on inertial motion sensors are promising methods, with the advantage compared to optoelectronic cameras of not being confined to a laboratory setting. A challenge is to develop relevant outcome measures for clinical use. The aim of this study was to characterize elbow and shoulder motion during functional tasks, using portable motion sensors and a modified Exposure Variation Analysis (EVA) and evaluate system accuracy with optoelectronic cameras. Ten healthy volunteers and one participant with sequel after stroke performed standardised functional arm tasks. Motion was registered simultaneously with a custom developed motion sensor system, including gyroscopes and accelerometers, and an optoelectronic camera system. The EVA was applied on elbow and shoulder joints, and angular and angular velocity EVA plots was calculated. The EVA showed characteristic patterns for each arm task in the healthy controls and a distinct difference between the affected and unaffected arm in the participant with sequel after stroke. The accuracy of the portable system was high with a systematic error ranging between −1.2° and 2.0°. The error was direction specific due to a drift component along the gravity vector. Portable motion sensor systems have high potential as clinical tools for evaluation of arm function. EVA effectively illustrates joint angle and joint angle velocity patterns that may capture deficiencies in arm function and movement quality. Next step will be to manage system drift by including magnetometers, to further develop clinically relevant outcome variables and apply this for relevant patient groups. Highlights: Portable motion sensors are promising tools for movement analysis. Transition from a technical research tool to a clinical tool is a major challenge. Exposure Variation Analysis of joint motion has the potential to be such a tool. For long-term measurements, magnetometers should be added to avoid drift.